2021
DOI: 10.1093/rpd/ncab105
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Metal Artefacts for Different Dual Energy Ct Techniques

Abstract: This study compares dual-energy computed tomography (DECT) images of a phantom including different material inserts and with additional lateral titanium or stainless steel inserts, simulating bilateral hip prostheses. Dual-source (DS) and fast kV-switching (FKS) DECT with/without metal artefact reduction (MAR) were compared with regards to virtually monoenergetic CT number accuracy and the depiction of different materials. Streak artefacts were observed between the metal inserts that were more severe with stee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 20 publications
2
3
0
Order By: Relevance
“…This seems to be different from dual-source and dual-layer spectral-detector CT. Similarly to the findings in rapid-kVp-switching DECT and other studies [ 47 , 48 ], overcorrection of artifact was also observed in spinal implants in our study when using iMAR, however to a much lesser degree. This may be because the iMAR algorithm, used in this study, combines beam hardening correction, normalized sinogram inpainting and frequency split, to address both, the avoidance of new artifacts and the conservation of the original image impression [ 5 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…This seems to be different from dual-source and dual-layer spectral-detector CT. Similarly to the findings in rapid-kVp-switching DECT and other studies [ 47 , 48 ], overcorrection of artifact was also observed in spinal implants in our study when using iMAR, however to a much lesser degree. This may be because the iMAR algorithm, used in this study, combines beam hardening correction, normalized sinogram inpainting and frequency split, to address both, the avoidance of new artifacts and the conservation of the original image impression [ 5 , 49 ].…”
Section: Discussionsupporting
confidence: 92%
“…During the evaluation process, we found that MAR technology could reduce beam hardening artifacts for the surrounding structures while causing certain distortion on screw itself, which is consistent with previous research results ( 12 , 27 , 29 ). Some scholars believed that this distortion of MAR could affect the judgment of screws and recommended to use a 140 keV monochromatic images in dual energy CT without the use of MAR when evaluating the metal screws.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, reducing the beam hardening artifacts of pedicle screws can better evaluate the condition of the bone and soft tissue around the metal screws, helping orthopedic doctors and radiologists to make more accurate evaluations of the surgical effect and condition ( 9 - 11 ). At present, the commonly used methods for removing metal beam hardening artifacts often rely on the use of high energy photons with either high tube voltage or high energy virtual monoenergetic images in dual-energy CT ( 12 - 14 ), or the combination of metal artifact reduction (MAR) technology with reconstruction algorithms to further significantly reduce beam hardening artifacts and improve diagnostic effectiveness ( 15 - 18 ). However, in order to generate adequate signal when taking images of metals, radiation dose is usually relatively high.…”
Section: Introductionmentioning
confidence: 99%
“…is not yet fully understood and is under active investigation. A possible alternative solution would be dual-energy CT, which has been proven to reduce metal artifacts and quantify the material property more accurately [20] [21] [22].…”
Section: Discussionmentioning
confidence: 99%